Eliciting Public Support for Greening the Electricity Mix Using Random Parameter Techniques - Peter Grösche; Carsten Schröder (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
With its commitment to double the share of renewable fuels in electricity generation to at least 30% by 2020, the German government has embarked on a potentially costly policy course whose public support remains an open empirical question. Building on household survey data, in this paper we trace peoples' willingness-to-pay (WTP) for various fuel mixes in electricity generation, and capture preference heterogeneity among respondents using random parameter techniques. Based on our estimates, we trace out the locus that links the premia charged for specific electricity mixes with the fraction of people supporting the policy. Albeit people's WTP for a certain fuel mix in electricity generation is positively correlated to the renewable fuel share, our results imply that the current surcharge effectively exhausts the financial scope for subsidizing renewable fuels.
Keywords: C23; H23; Q48; 330; green electricity; willingness-to-pay; preference heterogeneity; policy evaluation